2022
DOI: 10.1038/s41586-022-05066-5
|View full text |Cite|
|
Sign up to set email alerts
|

Truncated FGFR2 is a clinically actionable oncogene in multiple cancers

Abstract: Somatic hotspot mutations and structural amplifications and fusions that affect fibroblast growth factor receptor 2 (encoded by FGFR2) occur in multiple types of cancer1. However, clinical responses to FGFR inhibitors have remained variable1–9, emphasizing the need to better understand which FGFR2 alterations are oncogenic and therapeutically targetable. Here we apply transposon-based screening10,11 and tumour modelling in mice12,13, and find that the truncation of exon 18 (E18) of Fgfr2 is a potent driver mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 113 publications
0
48
0
2
Order By: Relevance
“…For the proteomic and phosphoproteomic analyses of KB1P(M) tumors, we used previously published proteomics dataset generated by MS (PRIDE accession code: PXD032007) (Zingg et al, 2022). For phosphoproteomic analysis, For phosphoproteomic analysis, MaxQuant phosphosite quantification data (Phospho (STY)Sites.txt) was log2-transformed, normalized on the median intensity of all identified phosphosites and replicates averaged favoring data presence.…”
Section: Methods Detailsmentioning
confidence: 99%
“…For the proteomic and phosphoproteomic analyses of KB1P(M) tumors, we used previously published proteomics dataset generated by MS (PRIDE accession code: PXD032007) (Zingg et al, 2022). For phosphoproteomic analysis, For phosphoproteomic analysis, MaxQuant phosphosite quantification data (Phospho (STY)Sites.txt) was log2-transformed, normalized on the median intensity of all identified phosphosites and replicates averaged favoring data presence.…”
Section: Methods Detailsmentioning
confidence: 99%
“…Moreover, PTEN deletion activates the PI3K/AKT/mTOR pathway, which is the most common molecular mechanism of CRPC and one of the causes of ADT resistance 18 . Fibroblast growth factor receptor 2 (FGFR2), has often happened somatic hotspot mutations, structural ampli cation and fusion in multiple cancers 19 . A previous study found that the loss of FGFR2 is related to the malignant progression of prostate cancer and it will be a clinical therapeutic target 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the inactivation of FGFR signaling would be more effective in consistently inhibiting cancer cell growth in a clinical situation where JAK/STAT pathway is significantly downregulated in tumors. Zingg et al (2022) identified a clinically actionable mutation in FGFR2. They performed a transposon-based screening for cancer driver mutations and observed the truncation of exon 18 (E18) at Fgfr2 (Fgfr2 ΔE18 ) in mice.…”
mentioning
confidence: 99%
“…This steady growth is because the efficacy of FGFR inhibitors is low, and clinical responses to the agents are inconsistent ( Katoh, 2019 ). Clues for the clinical variability of the drugs were provided in two recent papers, facilitating the appropriate use of FGFR inhibitors ( Chan et al, 2022 ; Zingg et al, 2022 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation